Does the correspondence between EQ-5D health state description and VAS score vary by medical condition? - Whynes, David K. (BioMed Central, 2013)
Background The EQ-5D health-related quality of life instrument comprises a health state classification (health problems by severity in five domains), followed by an evaluation using a visual analogue scale (VAS). Despite the EQ-5D’s use in health technology assessment and as a patient-reported outcome measure (PROM), the correspondence between the two parts of the instrument remains ill-understood. In this paper, we consider whether the association between health state classification and VAS score might vary by medical condition.